Ant-based contention resolution in slotted WDM optical packet switched networks - Tan, Saw Chin; Abbou, F. M.; Ewe, Hong Tat (The Institute of Electronics, Information and Communication Engineers, 2006)
This paper proposed an Ant-based contention resolution scheme for the slotted optical packets switched (OPS) networks. The proposed contention resolution schemes are shown to be effective to resolve packet contention and to achieve good performance by using minimum number of fiber delay lines (FDL). Moreover, the cell loss rate is improved by 10% to 40% under various traffic loads using the proposed scheme.